Dietary Choline-Enhanced Skin Immune Response of Juvenile Grass Carp Might Be Related to the STAT3 and NF-kB Signaling Pathway (Ctenopharyngodon idella) - Yuan, Ze-Hong; Feng, Lin; Jiang, Wei-dan; Wu, Pei; Liu, Yang; Jiang, Jun; Kuang, Sheng-yao; Tang, Ling; Zhou, Xiao-qiu (Frontiers in Nutrition, 2021)
To investigate the effects and potential mechanisms of dietary choline on immune function in the skin of juvenile grass carp (Ctenopharyngodon idella), fish were fed different diets containing different levels of choline (142.2, 407.4, 821.6, 1215.8, 1589.3, and 1996.6 mg/kg) for 70 d, and then sampled after a 6-d challenge test. The results exhibited that dietary choline (1) advanced the contents of phosphatidylcholine (PC), betaine, and choline in grass crap skin (P < 0.05), up-regulated the mRNA abundance of choline transporter high-affinity choline transporter 1 (CHT1), choline transporter-like protein 1 (CTL1), and choline transporter-like protein 5 (CTL5), indicating that dietary choline could increase the contents of choline might be connected with choline transporters in the grass carp skin; (2) receded skin rot symptom after infection with A. hydrophila (Aeromonas hydrophila) and increased the level of IgM, C4, C3, and the activities of acid phosphatase (ACP) and lysozyme activity (LZ), raised mucin2, β-defensin, hepcidin, and LEAP-2B mRNA abundance (rather than LEAP-2A), down-regulated pro-inflammatory cytokines mRNA abundance (IFN-γ2, IL-15, TNF-α, IL-6, IL-12P40, and IL-1β) in skin of juvenile grass carp (P < 0.05), up-regulated anti-inflammatory cytokines mRNA abundance ( IL-10, IL-4/13A, TGF-β1, IL-11, and IL-4/13B) in grass crap skin (P < 0.05), demonstrating that choline enhanced the skin immune function; and (3) down-regulated the mRNA abundance of IKKγ, NF-κBp52, IKKβ, c-Rel, NF-κBp65, STAT3b2, STAT3b1, JAK1, and JAK2 as well as protein level of NF-κBp65, p-STAT3 Tyr705, and p-STAT3 Ser727 in nucleus and inhibited the mRNA and protein level of IkBα (P < 0.05), indicating that choline enhanced immune function might be relevant to JAK1, 2 /STAT3 and NF-κB signaling pathway in fish skin; In conclusion, choline enhanced the skin immune function might be relate to JAK1, 2/STAT3 and NF-κB signaling molecules in fish. Furthermore, based on immune indices of grass carp (9.28-108.97g) skin (C3 and IgM contents as well as ACP activities), the choline requirements were estimated to be 1475.81, 1364.24, and 1574.37 mg/kg diet, respectively.